Helen of Troy : and other poems - Tsaloumas, Dimitris, 1921- (University of Queensland Press, 2007)
Moving effortlessly between the Greek Islands and suburban Australia, these poems cross and recross the borders of structure and chaos, life and death, inner and outer worlds, dislocation and belonging. Displaying elaborate splendor, the centerpiece of this poet's last collection in English is the breathtaking sequence A Winter Journey, containing great themes of the self, its world, its art, its journeys, and its failures.